ANALISIS SPASIAL DAN VISUAL INTEGRASI JOGLO SEBAGAI RUANG TAMU PADA BANGUNAN CAMPURAN (MIXED-USE) BERGAYA MODERN - Atsiil Putra Utama; Eko Suwarno; Aulia Rahma Efendi; Aura Aldamah Dea; Azizah Nur Kamila; Tee Tze Kiong (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The current trend toward modern minimalist architecture in Indonesia often leads to the erosion of local values and the loss of cultural relevance in contemporary buildings. This phenomenon poses significant challenges for mixed-use building typologies such as Small Office Home Office (SOHO) spaces, particularly regarding the organization of circulation patterns and the protection of privacy between professional and domestic spheres. This study aims to evaluate the use of a detached Joglo structure as both a reception area and a privacy screen for the upper-floor residence. Through a descriptive qualitative case study method, this research analyzes design technical documents using spatial syntax, mass morphology, and user movement analysis. The analysis reveals that the integration of the standalone Joglo structure effectively creates a buffer zone that enhances spatial organization, thereby maintaining residents’ privacy without hindering office operations on the ground floor. This optimization of privacy management is achieved through contrasting vertical zoning and path engineering to minimize user cross-circulation. This research concludes that the application of neo-vernacular principles to the Joglo offers an adaptive design solution to the constraints of urban land, while maintaining a balance between cultural identity, commercial function, and residential comfort.